Mycotoxins occurrence in food commodities, their associated hazards and control strategies - Akbar, Ali; MAJEED, FATIMA ABDUL; Sadiq, MUHAMMAD Bilal; Khan, Shabir Ahmad; Rabaan, Ali A (Journal of the Hellenic Veterinary Medical Society, 2022)
Globally, the food is contaminated by various means but microorganisms are predominant factor in contaminating the food and agriculture commodities. Among microorganisms, fungi are mainly involved in the spoilage of food due to their diversified nature and minimal requirement for growth. The toxigenic fungi associated with mycotoxins, can grow during any stage of food chain including harvesting, handling, distribution and storage. Mycotoxins are fungal secondary metabolites and their production is influenced by various factors such as environmental conditions, crop type and storage conditions. Mycotoxins in agriculture commodities expose serious health hazards. This review entails different types of mycotoxins involved in the spoilage of food and agriculture commodities, their potential health hazard, maximum allowable limits of mycotoxins in different food commodities and possible control strategies. In developing countries, regulatory authorities need to establish quality control strategies and limits of mycotoxins in food, in order to ensure the consumer safety.